Creating Shade : Design, Construction, Technology - Uffelen, Chris van, 1966- (Braun Publishing, 2013)
Creating shade presents all conceivable types and forms of shade-providing design made of a host of different materials such as wood, fabrics, concrete, and a great number of synthetic materials. The collection includes elegant pergolas, extravagant pavilions, and roofed piazzas, as well as a fascinating solution for a canopy over a Roman excavation site and the spectacular Metropol Parasol in Seville. Outstanding serial products are presented along with individually constructed creations."--Dust jacket